TULAREMIA ANALYSIS, KANSAS, 2012-2015 - Paquette, Callie (My University, 2016)
Tularemia is a zoonotic disease caused by the bacteria Francisella tularensis that is endemic in the United States. With the potential to cause severe illness and even death as well as concern for its use as a biological weapon of warfare, tularemia is a mandated reportable disease. Tularemia can be transmitted to humans through exposure to other infected small mammals, ticks, deerflies, or contaminated soil or water. Although tularemia is a relatively rare disease investigation into the incidence rate and causes are important for identifying changes in the typical disease trend of tularemia. The goal of this field experience and project with the Kansas Department of Health and Environment (KDHE) was to perform quality assessment and analysis of data regarding tularemia infections in Kansas between the years 2012 to 2015. Data was assessed for commonalities among cases that would provide the KDHE with an in-depth understanding of tularemia in Kansas. The data analyzed in this report was compared to a report done by the Centers for Disease Control and Prevention (CDC) regarding tularemia in the United States from 2001 to 2010. Overall, the 2012-2015 Kansas tularemia analysis was comparable to the CDC analysis in 2010, with the exception of a 345 percent increase in tularemia incidence in Kansas. The findings from this report may be used to enhance the KDHE’s knowledge of tularemia in Kansas. As well as provide a background for healthcare providers to improve awareness and prevention methods across Kansas.
Keywords: Tularemia; Kansas; Zoonotic; Reportable; Kansas Department of Health and Environment